In vitro gastrin-releasing peptide response in chicken ovarian follicles - Chunheng Mo; Can Lv; Guoqiang Zhu; Jiannan Zhang; Yuanyou Li; Yajun Wang; Juan Li (Poultry Science, 2025)
The gastrin-releasing peptide (GRP) is reported to be mainly produced by the pituitary in chickens, with its receptor (GRPR) highly expressed in the ovaries, indicating its regulatory role in ovarian function. Present study aims to verify the role of GRP and GRPR in regulating the growth of ovarian follicles in chickens in vitro. GRPR was found to be highly expressed in granulosa cells of early follicles (1-6 mm), but shows barely detectable expression in theca cells. Moreover, in cultured granulosa cells isolated from early ovarian follicles, GRP peptide can activate the intracellular MAPK/ERK signaling pathway, thereby promoting granulosa cell proliferation. It was demonstrated that GRP enhanced the expression of Heparin-Binding EGF-like growth factor (HB-EGF), a local ovarian mediator that stimulates granulosa cell proliferation. The finding that GRPR is predominantly expressed in early follicles granulosa cells (1-6 mm), contrasts that of follicle-stimulating hormone receptor (FSHR) and luteinizing hormone receptor (LHR) being mainly abundantly expressed in granulosa cells of late follicles (F5 and F1). The present study supports the notion of coordination between GRP peptide and gonadotropins (LH and FSH) in promoting chicken follicular development.